Research on the quantitative relationship between stress shadow effect of multiple thick and hard key layers and surface subsidence - Jianqiao Luo; Yupeng Shen; Xin Meng; Tuo Yang (Scientific Reports)
Abstract For a long time, the management of surface structures such as villages and rivers affected by underground coal mining has been a popular and difficult issue in coal mining. With the further tightening of environmental protection requirements, it has become challenging for some underground coal mines that lack the conditions for filling and grouting to ensure the recovery of coal resources while controlling surface subsidence. Furthermore, many such common issues have emerged in the Yushen and Binchang mining areas of Shanxi Province, as well as in several other coalfields, severely constraining the development of coal energy and ecological environmental protection. Research on numerical simulation experiments and theoretical calculations via mechanical models suggests that the presence of multiple thick and hard key strata in the overlying rocks plays a crucial role in controlling surface displacement through the interlayer shading effect. A comparison of three mining methods, namely, fully mechanized top-coal caving with a large mining height (CMTC), longwall mining with a large mining height and full-height cutting (LMHT), and layered fully mechanized top-coal caving (LCMTC), reveals peak surface displacements of 3.818 m (CMTC), 3.649 m (LMHT), and 3.32 m (LCMTC), respectively, and peak vertical stresses of 7.3 MPa (CMTC), 5.9 MPa (LMHT), and 8.3 MPa (LCMTC), respectively. Based on these findings, an artificial buffer layer technology for controlling overlying rock displacement is proposed. This technology has a significant effect on effectively controlling surface subsidence by releasing stress in the overlying rock and provides a theoretical reference and methodological insights for mines with similar operating conditions.